Differential effects of hypoxia on motility using various in vitro models of lung adenocarcinoma - Sára Eszter Surguta; Marcell Baranyi; Laura Svajda; Mihály Cserepes; Ivan Ranđelović; Enikő Tátrai; Balázs Hegedűs; József Tóvári (Scientific Reports)
Abstract Lung cancer is the leading cause of cancer-related death globally. Metastasis is the most common reason of mortality in which hypoxia is suggested to have a pivotal role. However, the effect of hypoxia on the metastatic potential and migratory activity of cancer cells is largely unexplored and warrants detailed scientific investigations. Accordingly, we analyzed changes on cell proliferation and migratory activity both in single-cell migration and invasion under normoxic and hypoxic conditions in lung adenocarcinoma cell lines. Alterations in crucial genes and proteins associated with cellular response to hypoxia, epithelial-mesenchymal transition, proliferation and apoptosis were also analyzed. Generally, we observed no change in proliferation upon hypoxic conditions and no detectable induction of apoptosis. Interestingly, we observed that single-cell motility was generally reduced while invasion under confluent conditions using scratch assay was enhanced by hypoxia in most of the cell lines. Furthermore, we detected changes in the expression of EMT markers that are consistent with enhanced motility and metastasis-promoting effect of hypoxia. In summary, our study indicated cell line-, time of exposure- and migrational type-dependent effects of hypoxia in cellular proliferation, motility and gene expression. Our results contribute to better understanding and tackling cancer metastasis.